Problemy sportivnogo otbora junyh begunov na korotkie distancii - Yushkevich, T.; Baranayev, Y. (Science in Olympic Sport, 2020)
The article deals with the problems of sports selection of promising children for practicing track and field in the CYSS. The results of a longitudinal study of sprinters in the age range of 12-17 years are presented. The author's complex methodology for predicting the motor abilities of young sprinters was used. A comprehensive method for predicting the motor abilities of sprinters at the stage of initial sports specialization consisting of three components was developed with account for the most informative indices that determine the prospects of young athletes. The first component is a complex testing of young sprinters using the most informative indices that determine the level of prospects. Testing is carried out in three stages (at the beginning of the preparatory period, during the second competitive period of athletes of the 1st year of training, and during the second competitive period of athletes of the 2nd year of training); the second component - assessment of prospects (preliminary, intermediate, final), calculated in points using the developed formulas; the third component - selection into training groups based on the assessment of the prospects of athletes (differentiation is carried out in training groups, identifying the potential and forecasting the motor abilities of sprinters, staffing training groups). The results of the pedagogical experiment showed the effectiveness of this methodology. It is noted that an objective assessment of the prospects of young athletes can be obtained only on the basis of complex studies. The developed methodology may be modified later on. However, there is reason to believe that the general nature of the research has already allowed obtaining objective data, on the basis of which an attempt was made to equip practitioners of physical culture and sports with a comprehensive method of predicting motor abilities of sprinters at the stage of initial sports specialization with account for the most informative indices that determine the prospects of young athletes.